Local Employment in Tourist Attraction: A Community Perspective - Amanda Rizka Rachim (Journal of Tourism Sustainability, 2022)
Participation of local communities is a criterion that is often agreed upon as an important condition for the development and sustainability of all forms of tourism. Local employment becomes one form of recruitment that tourist attractions often carry out. However, increasing local participation in tourism often creates friction between tourist attractions and residents. This research aims to explore local participation in The Lodge Maribaya, one of the popular tourist attractions in Bandung West Java, by investigating factors influencing the community's support for local employment in the area. Data was collected using a structured questionnaire from 59 employees who are locals in the area. The confirmatory factor analysis was utilized to test the construct validity and reliability of the model. At the same time, Partial Least Squares (PLS) modeling was employed to assess the relationship among the variables. This study has found that community attachment and perceived benefits play an important role in the community's support in The Lodge Maribaya in terms of their participation in local employment. The strong community attachments and the considerable benefits perceived by the community are cogitated to be the main factors in The Lodge Maribaya's success in employing local workers. By investigating this perspective, this study is expected to provide insights on how to increase local participation in employment and anticipate the aspect that may hinder the process